Improving Mockup-Based Requirement Specification with End-User Annotations - Urbieta, Mario Matías (2018)
Agile approaches, one of the key methodologies used in today’s software projects, often rely on user interface mockups for capturing the goals that the system must satisfy. Mockups, as any other requirement artifact, may suffer from ambiguity and contradiction issues when several points of view are surveyed/elicited by different analysts. This article introduces a novel approach that enhances mockups with friendly end-user annotations that helps formalizing the requirements and reducing or identifying conflicts. We present an evaluation of the approach in order to measure how the use of annotations improves requirements quality.